Disruption of Health Services for Pregnant Women, Newborns, Children, Adolescents, and Women During the Covid-19 Pandemic: Islac 2020 Project [Interrupción de Servicios de Salud Para Embarazadas, Recién Nacidos, Niños y Niñas, Adolescentes y Mujeres Durante la Pandemia de Covid-19: Proyecto Islac 2020 - Castillo-Nara, A; Maddaleno-Herrera, M; Villalobos-Dintrans, P (Pan American Health Organization, 2021)
Objective. Describe the perceptions of key actors regarding the disruption of health services for populations that ceased to be prioritized because of the COVID-19 pandemic-pregnant women, newborn, children, adolescents, and women-in countries of Latin America and the Caribbean (LAC) during the first stage of the pandemic. Methods. In this cross-sectional study, a 35-question survey was administered to key actors in 19 LAC countries between July and September 2020. The respondents were asked for their personal perceptions regarding the situation of social and health services in their country before and during the pandemic. They were also asked for a projection of the situation during the post-pandemic period. Results. In the 691 responses received, the main perception was that coverage in the services analyzed had been high before the pandemic, although their quality was not as highly rated. Both the coverage and quality of services were thought to have declined for adolescents and women. The majority of respondents predicted that all services will continue to function at lower than usual coverage levels for another three months (53.1%) and another 12 months (41.3%). Guaranteeing coverage and access to health services was considered the main policy challenge going forward. The next most needed initiatives noted were financing for actions to support women, children, and adolescents, and protection against violence and promotion of measures to combat it. Conclusions. Although the pandemic has struck all countries, its effect on the delivery of services in the populations analyzed differs from country to country and according to the types of service. It is essential to invest in national information systems that will make it possible to monitor the different services and identify the populations that need to be prioritized. © 2021 Pan American Health Organization. All rights reserved.